The Implementation Of Blockchain Technology In Improving Transparency And Reliability Of Financial Reporting - Indriyani, Kristi; Wijaya, Shirley (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the implementation of blockchain technology in financial reporting and assesses how it affects organizational financial systems' operational efficiency, dependability, and transparency. Blockchain technology offers a revolutionary method of documenting and confirming financial transactions because of its decentralized, immutable, and real-time ledger structure. The results show that by reducing data manipulation and guaranteeing traceable transaction records, blockchain adoption greatly improves the accuracy, consistency, and reliability of financial information. Businesses that have used blockchain-based financial reporting systems report significant gains in audit timeliness and efficiency as well as decreases in fraud risk, manual recording errors, and reconciliation problems. Verified financial data is readily available in real time, which helps stakeholders and management make better decisions. Despite these benefits, the study points out a number of obstacles that prevent widespread adoption, such as high implementation costs, difficult technological integration with outdated accounting systems, worries about data protection, and a lack of unified and transparent legal frameworks. In particular, regulatory uncertainty makes firms hesitant about legal accountability and compliance. The study's findings are in line with other research, supporting blockchain's potential as a game-changing financial reporting innovation. Future research should concentrate on creating scalable implementation models, improving system interoperability, and analyzing long-term cost-benefit implications, according to the study's conclusion. In order to promote the wider and more sustainable deployment of blockchain technology in the financial industry, legislators and standard-setting organizations are also urged to create thorough regulatory rules.